Sistem Pendukung Keputusan dengan Metode Analitycal Hierarchy Process (AHP) untuk Pemilihan Strategi Proses Produksi yang Efisien - Imam Husni Al Amin (Jurnal Ilmiah Dinamika Teknik, 2008)
Many and complicated criteria can result in problems in making a decision. Therefore. a method is needed to solve the problem. The method is Analytical Hierarchy Process (AHP). The existence of overflowing and complex criteria can result in problems in making a decision. Therefore, a method is needed to solve thc problem accurately and quickly. The method is Analytical Hierarchy Process (AHP) the principles of which begin hy decomposing problems of a complicated decision and categorizing them into certain hierarchical elements. The matrix elements in pairs which lie on the same hierarchy are compared by considering qualitative and quantitative factors (pair wise comparison). This AHP enables people 10 select the best alternatives based on the decision maker's intention and can combine deductive and systemic approaches in solving complicated problems